Determining the optimal vaccine vial size in developing countries: a Monte Carlo simulation approach. - Dhamodharan A; Proano RA; Dhamodharan, Aswin; Proano, Ruben A (Health Care Management Science, 2012)
Outreach immunization services, in which health workers immunize children in their own communities, are indispensable to improve vaccine coverage in rural areas of developing countries. One of the challenges faced by these services is how to reduce high levels of vaccine wastage. In particular, the open vial wastage (OVW) that result from the vaccine doses remaining in a vial after a time for safe use -since opening the vial- has elapsed. This wastage is highly dependent on the choice of vial size and the expected number of participants for which the outreach session is planned (i.e., session size). The use single-dose vials results in zero OVW, but it increases the vaccine purchase, transportation, and holding costs per dose as compared to those resulting from using larger vial sizes. The OVW also decreases when more people are immunized in a session. However, controlling the actual number of people that show to an outreach session in rural areas of developing countries highly depends on factors that are out of control of the immunization planners. This paper integrates a binary integer-programming model to a Monte Carlo simulation method to determine the choice of vial size and the optimal reordering point level to implement an (nQ, r, T) lot-sizing policy that provides the best tradeoff between procurement costs and wastage.